CORONARY ARTERY DISEASE IN OLDER WOMEN (World Bulletin of Public Health, 2024)
Younger women have a worse prognosis than older women, yet treating this condition is particularly challenging because older women have more comorbidities. For older women, coronary artery disease is the primary cause of both death and morbidity. Our goal is to talk about the characteristics and risk factors of CAD, which are important for both diagnosing and treating the condition.
Keywords: Coronary artery disease; Women; Obesity